Nanggulan Formation and Its Problem As a Basement in Kulonprogo Basin, Yogyakarta - Hill Gendoet Hartono; Adjat Sudradjat (Geological Agency, 2017)
DOI: 10.17014/ijog.4.2.71-80Nanggulan Formation consists of the oldest clastic rock sequence exposed in Kulonprogo area, Yogyakarta. This paper discusses the position of Nanggulan Formation as a basement. The method used in this research is surface and subsurface investigations based on gravity surveys. The rock assemblage is exposed and distributed partly in the east flank of Kulonprogo Mountains with weak undulated morphology. The rock sequence is composed of sand to clay grain sizes such as sandstone, quartz sandstone, calcareous sandstone, claystone, fossiliferous claystone, calcareous claystone, siltstone, and coal seam intercalations. The total thickness of the sequence is less than 200 m. Based on the fossil and palynology investigations, previous investigators concluded the age of the rock was Eocene to Middle Miocene. The geological structures developed in the rocks are the lithological stratification, fractures, folding, and faulting. The subsurface interpretation based on gravity data revealed the rock was located under the andesite breccias with 2.44 g/cc density. The density of the rock sequence was 2.63 g/cc. The gravity interpretation shows a strong indication that Nanggulan Formation underlies the andesitic breccias presumably associated with Old Andesite Formation exposed in Kulonprogo Mountains. The limited distribution, the thickness, and the closed environmental deposition of Nanggulan Formation found in the present investigation raised problems on the position of the formation as the basement of Old Andesite Formation occurring in the Kulonprogo Mountain.